Ohranjenost gozdnih tal in vegetacije v habitatu divjega petelina v vzhodnih Karavankah in vzhodnih Kamniško-Savinjskih Alpah - Kutnar, Lado (Zbornik gozdarstva in lesarstva, 2005)
In the high-montane zone of the eastern Karavanke range and the eastern Kamnik-Savinja Alps of Slovenia, the soil and vegetation conditions on nine representative plots in the Capercaillie (Tetrao urogallus L.) habitat were studied. The research was carried out on plots in different forest types within the Capercaillie leks, selected with regard to the different bedrock, exposure and level of forest degradation. By contrast to the well preserved beech forest, degradation processes in dystric soil on andesite tuff and gneiss of secondary spruce forest in the abandoned pastures were detected. In the forests on limestone and dolomite, the plant species diversity is much higher than in the forests on non-carbonate bedrock. On carbonate and non-carbonate bedrock, too, the level of preservation of forests (secondary forest in pastures vs. co-natural forests on permanent forest land) is significantly reflected in the floristic composition and vegetation structure.
Keywords: divji petelin; gozdna tla; Kamniško-Savinjske Alpe; Karavanke; vegetacija; visokogorski gozd